2015
DOI: 10.1002/ange.201502367
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mononuclear Non‐heme Iron(III)‐Superoxo Complex with a Five‐Azole Ligand Set

Abstract: Reaction of O 2 with ah igh-spin mononuclear iron(II) complex supported by af ive-azole donor set yields the corresponding mononuclear non-heme iron(III)-superoxo species,w hich was characterized by UV/Vis spectroscopya nd resonance Raman spectroscopy.1 HNMR analysis reveals diamagnetic nature of the superoxo complex arising from antiferromagnetic coupling between the spins on the low-spin iron(III) and superoxide. This superoxo species reacts with Hatom donating reagents to give al ow-spin iron(III)-hydropero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…The remaining 13% can be attributed to 1 and/or 4 , both of which are EPR-silent in ⊥-mode. Together, these results show that in contrast to the few reported Fe(III)-superoxo complexes, 2124 alkylthiolate-ligated 4 is capable of abstracting H atoms from strong C–H bonds, on par with that of the β C–H bonds of cysteine (93 kcal/mol). 33 It is plausible that π -back-donation by the electron-rich alkyl thiolate facilitates this reactivity by increasing the basicity of the distal oxygen.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The remaining 13% can be attributed to 1 and/or 4 , both of which are EPR-silent in ⊥-mode. Together, these results show that in contrast to the few reported Fe(III)-superoxo complexes, 2124 alkylthiolate-ligated 4 is capable of abstracting H atoms from strong C–H bonds, on par with that of the β C–H bonds of cysteine (93 kcal/mol). 33 It is plausible that π -back-donation by the electron-rich alkyl thiolate facilitates this reactivity by increasing the basicity of the distal oxygen.…”
mentioning
confidence: 62%
“…20 The former is proposed to involve the putative Fe(III)-superoxo, and the latter an Fe(IV)-oxo intermediate. 2 There are few well-characterized examples of Fe(III)-superoxo compounds, 2124 however, and none of these cleave strong C–H bonds. An aryl thiolate-ligated Fe–O 2 •− was recently reported; however, the sulfur lone pair is tied up in π -bonding to the aryl carbon in one of its resonance forms making it less reactive.…”
mentioning
confidence: 99%
“…2His enzymes are quite common and comprise the large class of 2His-1-carboxylate oxygenase enzymes along with α-ketoglutarate (α-KG)-dependent halogenase, which activates O 2 to carry out oxidative halogenations of nonactivated and activated carbon centers [813]. Several groups have worked on developing ligand systems to mimic these metal binding sites using Histidine mimics such as amine, amide, pyrrole, pyrazole, and pyridine [4,1416], however, it is anticipated that the imidazolyl group will be the best surrogate for histidine. Incorporation of bulky hydrophobic groups helps to mimic the hydrophobic environment often found at these sites.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Recently,m etal-superoxo species have attracted much attention in the communities of bioinorganic and biological chemistry,s ince the intermediates have been invoked as reactive species in the CÀHb ond activation and oxygen atom transfer reactions by nonheme iron and copper enzymes. [13][14][15][16][17][18][19] However,t he chemical properties of metal-superoxo species are less clearly understood and remain elusive in many respects.F or example, although mechanisms of hydride transfer from dihydronicotinamide adenine dinucleotide (NADH) analogues to highvalent metal-oxo complexes have been discussed recently, [20] hydride-transfer reactions by metal-superoxo complexes have never been explored previously.Additionally,although it has been shown that metal-superoxo complexes (M-O 2 C À )a re capable of abstracting ah ydrogen atom (H-atom) from substrates (that is,aone-electron oxidant), [21][22][23] there has been no example showing that metal-superoxo complexes (M-O 2 C À )can be athree-electron oxidant without achange in the oxidation state of metal ions. [13][14][15][16][17][18][19] However,t he chemical properties of metal-superoxo species are less clearly understood and remain elusive in many respects.F or example, although mechanisms of hydride transfer from dihydronicotinamide adenine dinucleotide (NADH) analogues to highvalent metal-oxo complexes have been discussed recently, [20] hydride-transfer reactions by metal-superoxo complexes have never been explored previously.Additionally,although it has been shown that metal-superoxo complexes (M-O 2 C À )a re capable of abstracting ah ydrogen atom (H-atom) from substrates (that is,aone-electron oxidant), [21][22][23] there has been no example showing that metal-superoxo complexes (M-O 2 C À )can be athree-electron oxidant without achange in the oxidation state of metal ions.…”
mentioning
confidence: 99%